THE ACCOUNTING EXCHANGE. - Holgate, H. C. F.; Yamey, B. S. (The Accounting Review, 1941)
It would be a strange business that could exist for any length of time without incurring risks, this essay will be confined to the audit of banks and similar financial institutions. Insofar as the ordinary commercial house is concerned it would not be unfair to state that contingent liabilities are comparatively unimportant the reason being, of course, that the direct liabilities that have definitely been incurred in the course of trading are usually much greater than the risks which may or may not arise as the result of some unforeseen contingency. A banking company that holds partly paid stock or shares in a Limited-Liability Company is liable in case of need to pay up the "calls" made upon shareholders, and it is therefore easy to assess the bank's risk under this heading. The audit should include an inspection of the stock and a careful examination of its wording. The current accounting practice is to mention the amount for which the bank stands liable if a call of all the unpaid capital is made.